Method for producing copper oxide nanosheets by using PCB acid etching solution
By adding a reducing agent and alkali metal hydroxide to an acidic PCB etching solution to generate cuprous chloride precipitate, and using alkali metal carbonate to generate basic copper carbonate intermediate, high-purity copper oxide nanosheets are obtained by heating and stirring at low temperature. This solves the purity control problem in existing technologies and is suitable for the fields of electronics industry, energy storage, solar cells and chemical catalysts.
Patent Information
- Application Number
- CN202610454232.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-04-08
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2046-04-08
AI Technical Summary
Existing technologies are difficult to efficiently and cost-effectively recover high-purity copper oxide from PCB acid etching solutions, and also suffer from problems such as long process routes, difficulty in purity control, and impurity ions affecting product activity.
By adding a reducing agent and alkali metal hydroxide to the acidic PCB etching solution to adjust the pH value, cuprous chloride precipitate is generated, and basic copper carbonate intermediate is generated using alkali metal carbonate and alkali metal bicarbonate. Finally, copper oxide nanosheets are obtained by heating and stirring at low temperature.
The preparation of high-purity copper oxide nanosheets has been achieved, simplifying the process, reducing costs, and effectively removing impurity ions. It is suitable for the fields of electronics industry, energy storage, solar cells, and chemical catalysts.
Smart Images

Figure CN122079219B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of PCB acid etching solution treatment technology, specifically relating to a method for producing copper oxide nanosheets using PCB acid etching solution. Background Technology
[0002] Printed circuit boards (PCBs), as core components of electronic computer equipment, are widely manufactured using chemical milling processes. In this process, an acidic etching solution composed of hydrochloric acid (HCl) and copper chloride (CuCl2) is commonly used to etch the copper-clad laminate. This etching wastewater contains a large amount of copper (typically 10%–15% by mass). Improper disposal not only causes serious heavy metal pollution but also represents a significant waste of copper resources, resulting in both economic and environmental pressures.
[0003] Currently, some technological attempts have been made to recover copper from acidic etching wastewater. For example, mixing acidic etching solution with alkaline etching solution generated in the PCB industry can recover copper oxychloride, which can be used as an agricultural raw material. However, the added value of the products obtained by this method is limited, and the adaptability and purity control of the processing flow are insufficient.
[0004] Copper oxide, as an important functional inorganic material, is widely used in various fields, including as a sintering aid for ferrite materials in the electronics industry, an effective component of bactericides, a catalyst, and a pigment. Conventional methods for preparing high-purity copper oxide mainly fall into two categories: one is the pyrometallurgical process, which oxidizes metallic copper to copper oxide at around 800℃ in an air or oxygen atmosphere. This method is energy-intensive and requires demanding equipment. The other is the wet neutralization process, which uses alkali metal hydroxides to neutralize soluble copper salt solutions (such as copper chloride, copper nitrate, and copper carbonate), followed by precipitation and thermal decomposition to obtain copper oxide. PCB acidic etching wastewater contains high concentrations of copper chloride, which can be used as an excellent copper salt raw material for the wet process to produce copper oxide, thus realizing the resource utilization of wastewater. However, existing neutralization methods generally suffer from problems such as long process routes, easy product agglomeration, and difficulty in purity control. Especially when using waste etching solution as raw material, the presence of impurity ions may lead to low product activity and increased side reactions, making it difficult to meet the requirements of high-end applications such as the electronics industry.
[0005] Therefore, developing a short, high-purity, and environmentally friendly copper oxide preparation process that directly utilizes PCB acid etching solution as raw material has significant practical implications and application value. Summary of the Invention
[0006] The purpose of this invention is to provide a method for producing copper oxide nanosheets using an acidic PCB etching solution. Through the design of the experimental steps and the control of the reactant dosage, the Cu in the PCB acidic etching solution is controlled. 2+It is transformed into high-purity copper oxide nanosheets.
[0007] To achieve the above objectives, the present invention provides the following technical solution: One of the technical solutions of this invention is to provide a method for producing copper oxide nanosheets using an acidic PCB etching solution, comprising the following steps: A reducing agent is added to an acidic PCB etching solution, and then a solution containing alkali metal hydroxide is added to adjust the pH of the system to 1-2, causing cuprous chloride precipitate to form. The cuprous chloride precipitate is dissolved in ammonia, and alkali metal carbonates and / or alkali metal bicarbonates are added to make the total molar concentration of alkali metal carbonates and / or alkali metal bicarbonates in the system 0.9-2.0 mol / L. The mixture is heated and stirred to generate basic copper carbonate precipitate. The basic copper carbonate is dissolved in a solution with an alkali metal hydroxide concentration of 0.05-4.0 mol / L, and the mixture is heated and stirred to obtain copper oxide nanosheets.
[0008] Preferably, the reducing agent includes at least one of sodium sulfite, hydrazine hydrate, and ascorbic acid; after adding the reducing agent, the concentration of the reducing agent in the PCB acid etching solution is 1.5 to 4.0 mol / L.
[0009] Optionally, the PCB acid etching solution, after being mixed with the reducing agent, further includes a water dilution step.
[0010] Preferably, the alkali metal hydroxides are sodium hydroxide and / or potassium hydroxide.
[0011] Preferably, the concentration of the solution containing the alkali metal hydroxide is 0.05–4.0 mol / L.
[0012] Preferably, the concentration of the ammonia water is 22-25 wt.%.
[0013] Preferably, the alkali metal carbonate is sodium carbonate and / or potassium carbonate; the alkali metal bicarbonate is sodium bicarbonate and / or potassium bicarbonate.
[0014] Preferably, in the step of generating basic copper carbonate precipitate, the heating and stirring temperature is 70-90°C and the time is 0.5-2 hours.
[0015] Preferably, in the step of generating copper oxide nanosheets, the heating and stirring temperature is 70-90°C and the time is 0.5-2 hours.
[0016] Preferably, the precipitate obtained in each step is heated and washed with water to further improve the purity of the final copper oxide nanosheets.
[0017] The heating and washing step of this invention can remove impurity ions from the acidic etching solution of PCBs. The impurity ions include one or more of the following: iron ions, calcium ions, nickel ions, manganese ions, zinc ions, lead ions, chromium ions, sodium ions, and magnesium ions.
[0018] The second technical solution of the present invention provides an application of the above-mentioned method for producing copper oxide nanosheets using PCB acid etching solution in the fields of copper electroplating, energy storage, solar cells, or chemical catalysts.
[0019] The beneficial technical effects of the present invention are as follows: This invention utilizes a reducing agent to react with acidic waste etching solution for precipitation. During the precipitation process, by controlling the pH and the content of hydroxide and carbonate bases, copper ions are first converted into cuprous chloride and basic copper carbonate intermediates before decomposing into copper oxide nanosheets. This invention features a simple and low-cost process that can produce high-purity copper oxide nanosheets from PCB acidic waste etching solution without high-temperature calcination. The provided method is applicable to copper plating, energy storage, solar cells, and chemical catalysts in the electronics industry. Attached Figure Description
[0020] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0021] Figure 1 The image shows the XRD pattern of the copper oxide nanosheets prepared in Example 2.
[0022] Figure 2 The purity of copper oxide prepared in Examples 1, 2, 3, Comparative Example 1, and Comparative Example 2 is given.
[0023] Figure 3 The images shown are SEM images of the copper oxide nanosheets prepared in Example 2, where (A) to (C) are SEM images at different magnifications.
[0024] Figure 4 The images show the SEM images and elemental distribution diagrams of the copper oxide nanosheets prepared in Example 2, where (A) is the SEM image, (B) is the O elemental distribution diagram, and (C) is the Cu elemental distribution diagram. Detailed Implementation
[0025] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention. It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the present invention.
[0026] It should be noted that any aspects not described in detail in this invention are conventional practices in the field and are not the focus of this invention.
[0027] Furthermore, regarding the numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Any stated value or intermediate value within a stated range, as well as each smaller range between any other stated value or intermediate value within said range, are also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0028] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar to or equivalent to those described herein may be used in the implementation or testing of this invention.
[0029] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.
[0030] In the embodiments of this invention, concentrated ammonia water refers to ammonia water with a concentration of 25 wt.%.
[0031] The initial copper ion concentration in the PCB acidic waste etching solution used in the embodiments and comparative examples of this invention is 120 g / L.
[0032] Example 1 First, 29 g of sodium sulfite (0.23 mol) was added to 100 mL of acidic waste PCB etching solution. The pH of the mixture was adjusted to 1-2 by adding 100 mL of deionized water and 20 mL of 0.45 mol / L sodium hydroxide solution, resulting in cuprous chloride precipitate. The precipitate was added to 500 mL of deionized water, stirred for 30 min, and filtered. This process was repeated 5 times. Subsequently, 100 mL of concentrated ammonia was added to the precipitate to dissolve the cuprous chloride in the solution, and the filtrate was obtained by filtration. 10 g of anhydrous sodium carbonate powder (0.09 mol) was added to the filtrate, and the mixture was heated and stirred at 80 °C for 0.5 h to form basic copper carbonate. Then, 100 mL of 1 mol / L sodium hydroxide solution was added to the basic copper carbonate, and the mixture was heated and stirred at 80 °C for 0.5 h, filtered, and washed to finally obtain copper oxide.
[0033] Example 2 First, 42g of sodium sulfite (0.33mol) was added to 100mL of acidic waste PCB etching solution. The pH of the mixture was adjusted to 1-2 by adding 100mL of deionized water and 20mL of 0.45mol / L sodium hydroxide solution, resulting in cuprous chloride precipitate. The precipitate was added to 500mL of deionized water, stirred for 30min, and filtered. This process was repeated 5 times. Subsequently, 100mL of concentrated ammonia was added to the precipitate to dissolve the cuprous chloride in the solution, and the filtrate was obtained by filtration. 10g of anhydrous sodium carbonate powder (0.09mol) was added to the filtrate, and the mixture was heated and stirred at 80℃ for 0.5h to form basic copper carbonate. Then, 100mL of 1mol / L sodium hydroxide solution was added to the basic copper carbonate, and the mixture was heated and stirred at 80℃ for 0.5h, filtered, and washed to finally obtain copper oxide.
[0034] Example 3 First, 55g of sodium sulfite (0.44mol) was added to 100mL of acidic waste PCB etching solution. The pH of the mixture was adjusted to 1-2 by adding 100mL of deionized water and 20mL of 0.45mol / L sodium hydroxide solution, resulting in cuprous chloride precipitate. The precipitate was added to 500mL of deionized water, stirred for 30min, and filtered. This process was repeated 5 times. Subsequently, 100mL of concentrated ammonia was added to the precipitate to dissolve the cuprous chloride in the solution, and the filtrate was obtained by filtration. 10g of anhydrous sodium carbonate powder (0.09mol) was added to the filtrate, and the mixture was heated and stirred at 80℃ for 0.5h to form basic copper carbonate. Then, 100mL of 1mol / L sodium hydroxide solution was added to the basic copper carbonate, and the mixture was heated and stirred at 80℃ for 0.5h, filtered, and washed to finally obtain copper oxide.
[0035] Comparative Example 1 First, 29 g of sodium sulfite (0.23 mol) was added to 100 mL of acidic waste PCB etching solution. The pH of the mixture was adjusted to 1-2 by adding 100 mL of deionized water and 20 mL of 0.45 mol / L sodium hydroxide solution, resulting in cuprous chloride precipitate. The precipitate was added to 500 mL of deionized water, stirred for 30 min, and filtered. This process was repeated 5 times. Subsequently, 500 mL of deionized water and 4.5 mL of 98% sulfuric acid were added to the precipitate, and air was bubbled through for 3 h until the solid was completely dissolved. The filtrate was then obtained. 10 g of anhydrous sodium carbonate powder (0.09 mol) was added to the filtrate, and the mixture was heated and stirred at 80 °C for 0.5 h to form basic copper carbonate. Then, 100 mL of 1 mol / L sodium hydroxide solution was added to the basic copper carbonate, and the mixture was heated and stirred at 80 °C for 0.5 h, filtered, and washed to finally obtain copper oxide.
[0036] Comparative Example 2 First, 29 g of sodium sulfite (0.23 mol) was added to 100 mL of acidic waste PCB etching solution. The pH of the mixture was adjusted to 1-2 by adding 100 mL of deionized water and 20 mL of 0.45 mol / L sodium hydroxide solution, resulting in cuprous chloride precipitate. The precipitate was added to 500 mL of deionized water, stirred for 30 min, and filtered. This process was repeated 5 times. Then, 50 g of anhydrous potassium persulfate powder (0.33 mol) was added to 500 mL of deionized water until the precipitate was completely dissolved. The solution was filtered to obtain the filtrate. Subsequently, 10 g of anhydrous sodium carbonate powder (0.09 mol) was added to the filtrate, and the mixture was heated and stirred at 80°C for 0.5 h to form basic copper carbonate. Then, 100 mL of 1 mol / L sodium hydroxide solution was added to the basic copper carbonate, and the mixture was heated and stirred at 80°C for 0.5 h, filtered, and washed to finally obtain copper oxide.
[0037] Figure 1 The image shows the XRD pattern of the copper oxide nanosheets prepared in Example 2.
[0038] from Figure 1 As can be seen, there are two characteristic peaks at 35.6° and 38.8°, which correspond to the (111) and (002) crystal planes of CuO, respectively (PDF#97-004-3179), indicating that the present invention has successfully obtained copper oxide.
[0039] Figure 2 The purity of copper oxide prepared in Examples 1, 2, 3, Comparative Example 1, and Comparative Example 2 is given.
[0040] Figure 3 The images shown are SEM images of the copper oxide nanosheets prepared in Example 2, where (A) to (C) are SEM images at different magnifications.
[0041] Figure 3 The results show that the high-purity copper oxide sample is in the form of nanosheets.
[0042] Figure 4 The images show the SEM images and elemental distribution diagrams of the copper oxide nanosheets prepared in Example 2, where (A) is the SEM image, (B) is the O elemental distribution diagram, and (C) is the Cu elemental distribution diagram.
[0043] Figure 4 This indicates that Cu and O elements are uniformly distributed in the material.
[0044] Table 1 shows the content of impurities sodium, iron, nickel, zinc, lead, chromium, magnesium, calcium, manganese, arsenic, cadmium, silver, aluminum, and potassium in the materials of Examples 1, 2, 3, Comparative Example 1, and Comparative Example 2, as determined by atomic absorption spectrophotometer.
[0045] Table 1 As can be seen from Table 1, the method of the present invention can produce high-purity copper oxide, and the copper oxide produced in Example 2 has even higher purity.
[0046] This invention uses an oxidation-reduction method to remove impurities from PCB acidic waste etching solution to prepare copper oxide nanosheets. The obtained copper oxide nanosheets are basically free of basic copper carbonate and copper hydroxide. The method provided by this invention can obtain high-purity copper oxide nanosheets without high-temperature calcination treatment. The process is simple and low-cost.
[0047] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.
Claims
1. A method for producing copper oxide nanosheets using an acidic PCB etching solution, characterized in that, Includes the following steps: A reducing agent is added to an acidic PCB etching solution, and then a solution containing alkali metal hydroxide is added to adjust the pH of the system to 1-2, causing cuprous chloride precipitate to form. The cuprous chloride precipitate is dissolved in ammonia, and alkali metal carbonates and / or alkali metal bicarbonates are added to make the total molar concentration of alkali metal carbonates and / or alkali metal bicarbonates in the system 0.9-2.0 mol / L. The mixture is heated and stirred to generate basic copper carbonate precipitate. The basic copper carbonate is dissolved in a solution with an alkali metal hydroxide concentration of 0.05-4.0 mol / L, and the mixture is heated and stirred to obtain copper oxide nanosheets. In the step of generating basic copper carbonate precipitate, the heating and stirring temperature is 70-90°C, and the time is 0.5-2 hours. In the step of generating copper oxide nanosheets, the heating and stirring temperature is 70–90°C, and the time is 0.5–2 h.
2. The method for producing copper oxide nanosheets using the PCB acid etching solution according to claim 1, characterized in that, The reducing agent includes at least one of sodium sulfite, hydrazine hydrate, and ascorbic acid; after adding the reducing agent, the concentration of the reducing agent in the PCB acid etching solution is 1.5 to 4.0 mol / L.
3. The method for producing copper oxide nanosheets using the PCB acid etching solution according to claim 1, characterized in that, The alkali metal hydroxides mentioned are all sodium hydroxide and / or potassium hydroxide.
4. The method for producing copper oxide nanosheets using the PCB acid etching solution according to claim 1, characterized in that, The concentration of the solution containing the alkali metal hydroxide is 0.05–4.0 mol / L.
5. The method for producing copper oxide nanosheets using the PCB acid etching solution according to claim 1, characterized in that, The concentration of the ammonia water is 22-25 wt.%.
6. The method for producing copper oxide nanosheets using the PCB acid etching solution according to claim 1, characterized in that, The alkali metal carbonate is sodium carbonate and / or potassium carbonate; the alkali metal bicarbonate is sodium bicarbonate and / or potassium bicarbonate.
7. The method for producing copper oxide nanosheets using the PCB acid etching solution according to claim 1, characterized in that, The precipitates obtained in each step were washed with heated water to further improve the purity of the final copper oxide nanosheets.
Citation Information
Patent Citations
Method for preparing high-purity cupric oxide powder from acid cupriferous waste liquid
CN101549882A
Method for preparing nano copper oxide
CN105858709A
Anhydrous cuprous chloride production process
CN109626411A
Method for preparing high-purity low-chlorine copper powder by taking copper chloride etching waste liquid as raw material
CN118720157A
